Additions to the genus Stigeoclonium (Chlorophyta) as new records for Bangladesh - Khan, Mazibar Rahman; Islam, AKM Nurul (Bangladesh Journal of Plant Taxonomy, 2005)
Three taxa belonging to the genus Stigeoclonium (Chaetophorales, Chlorophyta) are described here as new records for Bangladesh, namely, Stigeoclonium amoenum var. novizelandicum, S. protensum and S. tenue var. uniforme. Key words: New records, Stigeoclonium, Chlorophyta, Chaetophoraceae, Bangladesh DOI: 10.3329/bjpt.v12i2.598 Bangladesh J. Plant Taxon. 12(2): 1-9, 2005 (December)